Virtual-reality-based social cognition and interaction training for patients with schizophrenia: A preliminary efficacy study - Shen, Zhi-Hua; Liu, Meng-Hui; Wu, Yue; Lin, Qian-Qian; Wang, Yong-Guang (Frontiers in Psychiatry, 2022)
Background Social cognition and interaction training (SCIT) is a psychosocial intervention program for patients with psychosis, designed to improve their social functioning by improving social cognition. Although the feasibility and efficacy of SCIT have been verified, patients with schizophrenia tend to suffer from motivational deficits and low treatment adherence. It has been suggested that using virtual reality (VR) technology might be effective in addressing these issues. In this study, we aimed to develop a VR-based SCIT and compare its efficacy with that of traditional SCIT. Materials and methods We developed a novel VR-based social cognition and interaction training (VR-SCIT) that combines traditional SCIT (TR-SCIT) intervention with VR technology. Participants were randomly assigned in a 1:1:1 ratio to the VR-SCIT (n = 28), TR-SCIT (n = 30), or waiting-list groups (n = 29). All treatments were combined with treatment-as-usual. Assessments of social cognition (i.e., Chinese version of Face-Affective Identification Task, Chinese version of Social Cognition Screening Questionnaire) and social functioning (i.e., Chinese version of Personal and Social Performance Scale) were administered from baseline to post-intervention. Results Patients receiving VR-SCIT and TR-SCIT showed a significantly greater improvement on the assessments of emotion perception (Cohen’s d was 1.66, 0.55, and 0.10 for VR-SCIT, TR-SCIT, and Waiting-list, respectively), hostile attributional bias (Cohen’s d was 0.48, 0.44, and 0.05 for VR-SCIT, TR-SCIT, and Waiting-list, respectively), metacognition (Cohen’s d was 1.66, 0.76, and 0.06 for VR-SCIT, TR-SCIT, and waiting-list, respectively), and social functioning (Cohen’s d was 1.09, 0.90, and 0.20 for VR-SCIT, TR-SCIT, and waiting-list, respectively) from baseline to post-intervention, compared to those in waiting-list group. Additionally, VR-SCIT showed an advantage over TR-SCIT in improving emotion perception and metacognition with higher treatment compliance. Conclusion These preliminary findings indicate that VR-SCIT is a feasible and promising method for improving social cognition and social functioning in patients with schizophrenia.